POSSIBILITIES OF LASER AND PHOTODYNAMIC THERAPY IN THE TREATMENT OF PURULENT-NECROTIC PROCESSES OF THE LOWER EXTREMITIES IN PATIENTS WITH DIABETES MELLITUS (World Bulletin of Public Health, 2023)
The article presents the results of clinical studies on the possibility of using laser and photodynamic therapy in the treatment of purulent-necrotic processes of the lower extremities in patients with diabetes mellitus. To this end, the authors conducted clinical studies of 110 patients operated in the department of purulent-septic surgery of the ASMI clinic. Studies have shown that after the opening of the purulent-necrotic process of the lower extremities in patients with diabetes mellitus with the use of laser therapy in combination with photosensitization, accelerated regression of inflammatory infiltration, complete cessation of purulent-necrotic discharge, wound cleansing and activation of regeneration processes
Keywords: Diabetic phlegmon; autopsy of the purulent-necrotic process